Influence of Selected Parameters on Eddy Currents Attenuation in Non-Destructive Inspection - Janousek, Ladislav (Communications - Scientific letters of the University of Zilina, 2013)
Eddy currents attenuation in conductive materials under non-destructive inspection is analyzed in the paper. Influence of selected parameters of the inspection on the attenuation is studied by numerical means. A circular driving coil is employed to induce eddy currents in conductive plates under harmonic excitation. Outer diameter of the coil is varied together with the clearance between the coil and a plate surface for two plates with different thickness. Attenuation of the eddy current density in plates is studied and the results are analyzed in absolute values and the normalized ones as well. It is demonstrated that the investigated parameters of the inspection have significant impact on the attenuation.